Analisis Postur Tubuh Pemotongan Daging Sapi dengan Metode Nordic Body Map dan Rapid Upper Limb Assessment - Muhammad Yohan Maghriza Firdaus; Asep Erik Nugraha (Fakultas Teknik, 2023)
Abstract Los Beef H. Jarkasih is an MSME engaged in beef trading. When the market management was successful, it turned out that there were complaints from butchers regarding their health. The initial assumption was that this was due to inadequate work facilities, such as meat cutting activities which were carried out in a standing position and carried out for a long period of time, namely 12 hours per day. This study aims to determine the risk of injury due to activities carried out by workers. The settlement method used is the Nordic Body Map and Rapid Upper Limb Assessment methods. Data collection is done by direct observation and in-depth observation when workers are carrying out work. The findings of the study showed that the NBM score was 46, which means the level of risk of injury is still low and no corrective action is needed. Then for the RULA score, which is 4, which means further research is needed and changes may be needed. Thus, it can be concluded that the posture of beef slaughter workers has a low level of risk and is not dangerous and workers do not need to improve their work posture.Keywords: work biomechanics, ergonomics, musculoskeletal disorders, NBM, posture, RULA